21st Century Learning Skills among Lecturers in Vocational College - Hamzah, Norhasyimah; Fazrulhelmi Ahmad, Muhammad; Syamimi Mohd Razali , Nur; Ain Ahmad Jamaludin, Noorrul (International Journal of Psychosocial Rehabilitation, 2020)
The twenty-first century learning is a learning that involves the ability to collect, retrieve, organize, and manage information. This learning technique also applies information-based methods and is able to produce accurate information using existing resources. This new method of learning is associated with the use of digital technology, inventive thinking, effective communication, and productivity. Twenty-first-century learning involves certain skills such as high-level thinking skills, communication, collaboration, reflection, and creativity. The implementation of this study has achieved the following five objectives: (i) (i) to identify the perceptions of the high-level thinking skills of the lecturers towards the twenty-first-century learning; (ii) to identify lecturers’ reflection skills and perceptions on the twenty-first-century learning; (iii) to identify the perceptions of the collaborative skills of the lecturers towards the learning; (iv) to identify the relationships between high-level thinking skills and lecturers’ reflection skills in the new method of learning; and (v) to identify the relationships between lecturers’ high-level thinking skills and collaborative skills in twenty-first-century learning. A quantitative method was adopted by means of questionnaires and descriptive methods. Based on the understanding and application of lecturers towards 21st-century learning, it involves three skills, namely high-level thinking skills, reflection skills, and collaborative skills. The results of the study indicate that the rate of adopting twenty-first-century learning is still moderate. This is due to the lack of understanding and control over twenty-first-century learning, and the lecturers are still practicing the twenty-first-century learning method known as a method of reducing a two-way interaction between lecturers and students of vocational colleges.